2023
DOI: 10.3390/ijms241612862
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Prevention of Ectopic Erythrophagocytosis by Cilostazol Mitigates Ferroptosis in NASH

Abstract: Hepatic iron overload (HIO) is a hallmark of nonalcoholic fatty liver disease (NAFLD) with a poor prognosis. Recently, the role of hepatic erythrophagocytosis in NAFLD is emerging as a cause of HIO. We undertook various assays using human NAFLD patient pathology samples and an in vivo nonalcoholic steatohepatitis (NASH) mouse model named STAMTM. To make the in vitro conditions comparable to those of the in vivo NASH model, red blood cells (RBCs) and platelets were suspended and subjected to metabolic and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…MAFLD constitutes a metabolic hepatic disease, where metabolic perturbations precede inflammatory mechanisms. Otogawa et al 18 and Park et al 19 , have reported that hepatic erythrophagocytosis results in inflammation during MAFLD. We have also reported extended erythrocyte changes during MAFLD 2022,39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAFLD constitutes a metabolic hepatic disease, where metabolic perturbations precede inflammatory mechanisms. Otogawa et al 18 and Park et al 19 , have reported that hepatic erythrophagocytosis results in inflammation during MAFLD. We have also reported extended erythrocyte changes during MAFLD 2022,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis of TLR9-induced pro-inflammatory erythrophagocytosis seems to be contradictory to previous studies with regard to MAFLD. In particular, previous studies claimed that solely iron is responsible for hepatic erythrophagocytosis-induced inflammation 18,19 . However, iron alone is not sufficient for triggering ferroptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 149 ] Cilostazol, an antiplatelet drug, was also found to alleviate liver fibrosis through inhibiting hepatocyte ferroptosis via the prevention of ectopic erythrophagocytosis. [ 150 ] However, studies focused on the drugs targeting hepatocyte ferroptosis are still very limited.…”
Section: Liver Fibrosismentioning
confidence: 99%
“…Elevated levels of cAMP and/or cGMP have been found to have antifibrotic effects by inhibiting the myofibroblast-driven ECM production. Thus, several PDE inhibitors have been used to investigate the antifibrotic effects in different liver fibrosis animal models. For example, the PDE5 inhibitor tadalafil could improve portal hypertension and reduce liver fibrosis induced by bile duct ligation (BDL) in rats. , The PDE3 inhibitor cilostazol could protect rats from alcohol-induced liver fibrosis by suppressing the TGF-β/CTGF activation and the cAMP/EPAC1 signal. , Our group developed a PDE9 inhibitor 4a , which showed significant antifibrotic effects in a BDL-induced rat model …”
Section: Introductionmentioning
confidence: 99%